The ecto-enzyme CD38 is a nicotinic acid adenine dinucleotide phosphate (NAADP) synthase that couples receptor activation to Ca2+ mobilization from lysosomes in pancreatic acinar cells. - Cosker, F; Cheviron, N; Yamasaki, M; Menteyne, A; Lund, F; Moutin, M; Galione, A; Cancela, J (2010)
Nicotinic acid adenine dinucleotide phosphate (NAADP) is the most potent Ca(2+)-mobilizing intracellular messenger and is linked to a variety of stimuli and cell surface receptors. However, the enzyme responsible for endogenous NAADP synthesis in vivo is unknown, and it has been proposed that another enzyme differing from ADP-ribosyl cyclase family members may exist. The ecto-enzyme CD38, involved in many functions as diverse as cell proliferation and social behavior, represents an important alternative. In pancreatic acinar cells, the hormone cholecystokinin (CCK) stimulates NAADP production evoking Ca(2+) signals by discharging acidic Ca(2+) stores and leading to digestive enzyme secretion. From cells derived from CD38(-/-) mice, we provide the first physiological evidence that CD38 is required for endogenous NAADP generation in response to CCK stimulation. Furthermore, CD38 expression in CD38-deficient pancreatic AR42J cells remodels Ca(2+)-signaling pathways in these cells by restoring Ca(2+) mobilization from lysosomes during CCK-induced Ca(2+) signaling. In agreement with an intracellular site for messenger synthesis, we found that CD38 is expressed in endosomes. These CD38-containing vesicles, likely of endosomal origin, appear to be proximal to lysosomes but not co-localized with them. We propose that CD38 is an NAADP synthase required for coupling receptor activation to NAADP-mediated Ca(2+) release from lysosomal stores in pancreatic acinar cells.